Performance Analysis of the K-Nearest Neighbor (K-NN) Method in Classifying Hajj Pilgrims Service Satisfaction - Amalia, Nova; Nurdin, Nurdin (Jurnal Media Informatika, 2024)
This research examines the satisfaction of Hajj pilgrims from the city of Lhokseumawe using the K-Nearest Neighbors (K-NN) method. The satisfaction survey covers service dimensions such as accommodation, transportation, religious guidance, and healthcare. Qualitative data from the survey were transformed into numerical format, normalized, and partitioned into training and testing datasets. The K-NN algorithm was employed to classify satisfaction levels, with the optimal value of K determined through cross-validation. The findings demonstrate the effectiveness of the K-NN method in identifying satisfaction patterns and key influencing factors. Model evaluation utilizing metrics such as accuracy and precision indicates satisfactory performance, with an accuracy rate of 82,31% achieved through 10-fold cross-validation. Strategic recommendations are proposed based on the analysis to enhance the quality of Hajj services. This study provides deeper insights into the service aspects requiring improvement to enrich the pilgrimage experience for Hajj pilgrims.